ON SLEEP APNEA DIAGNOSIS: A WAVELET BASED APPROACH UTILIZING ECG DATA - SYEDA , QURATULAIN ALI (2013)
Sleep apnea is a nocturnal ailment related to breathing. An episode of sleep apnea is said to occur when a person does not breathe for more than 10 seconds. According to several epidemiological surveys, almost 3-7% of adult man and 2- 5% of adult females suffer from sleep apnea globally. Unfortunately, the traditional diagnosis of sleep apnea using Polysomnography is quite inconvenient and expensive. Therefore, research directions are turning towards signal processing based diagnosis of sleep apnea. Several researchers have contributed unique algorithms in this domain deploying different physiological signals. ECG is also being explored by many researchers for sleep apnea diagnosis. Critical literature review reveals that there still exists scope for a simpler, faster and memory efficient method for sleep apnea diagnosis using ECG signal.